Monetary Policy in the Presence of Islamic Banking - El Hamiani Khatat, Mariam (IMF Working Papers; Working Paper ;, 2016)
This paper discusses key issues related to the conduct of monetary policy in countries that have Islamic banks. It describes the macrofinancial background and monetary policy frameworks where Islamic banks typically operate, and discusses the monetary transmission mechanism in economies where Islamic and conventional banking coexist. Most economies with Islamic banks also have conventional banks and this calls for a comprehensive approach to monetary policy. At the same time, a dual approach to monetary policy should be considered whenever the Islamic segment of the financial system is not as developed as the conventional one. The paper tries to shed light on potential spillovers between conventional and Islamic financial systems, and proposes specific recommendations on the design of Islamic monetary policy operations and for facilitating monetary transmission through the Islamic financial system.